Tin-based halide perovskite nanocrystals: challenges, opportunities, and future directions - Pareja-Rivera, Carina; Pino, Fabián; Girón-Juárez, Karen Hatziri; Mora-Seró, Iván; Masi, Sofia (Frontiers in Materials, 2025)
Tin halide perovskite nanocrystals (THP-NCs) provide a pathway to defy the limitations of lead-based equivalents through their lower toxicity and direct bandgaps suitable for near-infrared (NIR) emissions. Thus far, most studies have been limited to stabilizing the material under environmental conditions. This problem can be attributed to the fast oxidation of Sn2+ to Sn4+, creating high defect density, particularly in tin vacancies, which act as nonradiative recombination centers, implying a lower photoluminescence quantum yield (PLQY) of around 1%. However, to fully uncover the potential of this material system, explorations of more complex synthesis and their properties, both as single materials and in combination with others in optoelectronic systems, will be essential. The THP-NCs were synthesized using different methodologies, such as hot injection, ligand-assisted reprecipitation, and chemical vapor deposition. These have permitted the adjustment of precursor chemistry, ligand engineering, and doping to reduce this limitation partially. Approaches, like appropriate conditions such as Sn-rich reactions and passivation of surface defects, have shown a potential to enhance stability and optical properties. In this Perspective, we summarize state-of-the-art approaches to synthetize the THP-NCs and highlight existing knowledge gaps and opportunities in their synthesis and characterization. We also propose a roadmap to accelerate the discovery of more stable materials with environmental robustness and predictable properties via the synergistic combination of experimental and computational efforts to achieve defect-tolerant THP-NCs with improved PLQY. Finally, we identify research opportunities and open questions in developing of next-generation Sn-based materials, optoelectronic devices, innovative systems that can bridge the gap between synthesizing and implementing these materials in real-world engineering applications.